PERBANDINGAN TINGKAT KESEGARAN JASMANI SIWA KELAS V SDN 012 HARAPAN JAYA DENGAN SISWA SDN 010 KARYA MUKTI KABUPATEN ROKAN HILIR - Lendra, Muhammad; ', Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this study originated from differences in the location of the school, students' physical activity, facilities and infrastructure in schools so that the resulting differences in physical fitness level of the students of SDN 012 Harapan Jaya and SDN Karya Mukti 0101. However, in the absence of accurate data on the level of physical fitness student researcher interested in conducting research on these issues. Therefore, the purpose of this study was to determine whether there are differences in the level of physical fitness at students class V SDN 012 and SDN 010 Harapan jaya Karya Mukti Rokan Hilir District. This type of research is classified in Comparative research, Sugiono in Ridwan (2002: 50) argues that "Comparative research is research that aims to compare the results of the two groups of data". The research data was obtained from the measurement results TKJI test. The sample in this study is the female students class V from each school totaling 28 people (purposive sampling). Based on the research results can be concluded as follows: Once t test then obtained thitung (2.49)> t table (2.179), where Ho is rejected and Ha is received, it can be concluded that there are differences in the physical fitness of students SDN 012 Harapan Jaya SDN 010 KaryaMukti Rokan Hilir District, where the level of physical fitness of students SDN 012 Harapan Jaya better when compared with students of SDN 010 Karya Mukti Rokan Hilir.Keywords : Comparison, Level, Physical Fitness